ANALISA KESTABILAN MODEL PENYEBARAN PENYAKIT RABIES - Rumlawang, Francis Y.; Nanlohy, Mario I. (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2011)
Rabies is a dangerous disease that can cause death due to rabies virus attacks the spinal cord of the infected and can cause paralysis. But if it enters the limbic system or midbrain, it will cause aggression and loss of sense. The widespread dissemination of this disease is growth increasingly. This research will discuss about the model of the spread rabies and then analyze stability of this model by using simple epidemiological model to determine the initial equilibrium point and eigenvalues, which would be analyzed the stability of this model. This model has two main variables and , where is the susceptible and is the infectives. This research found the stability model at ( ) equilibrium point with the value of parameter is âˆš .